Status quo and opportunities for multinutrient biofortification of maize in Africa - CGIAR Research Program on Maize (2021)
Key content: Synopsis of sub-Saharan populations' health challenges associated with Zn, provitamin A and tryptophan deficiencies; synthesis of past and present intervention measures; a discussion of the multinutritional maize strategy.